UPAYA PENURUNAN KEJADIAN STUNTING MELALUI EDUKASI MANAJEMEN LAKTASI PADA IBU HAMIL DAN POST PARTUM - Nurhannifah Rizky Tampubolon; Tari Audina; Nadhila Nurmaef; Yossy Garanetha; Fara Karnoni; Dinda Hirosehaya (Jurnal LENTERA, 2023)
Lactation management is one of the promotive and preventive efforts to overcome problems in the breastfeeding process so that the benefits of breastfeeding are achieved more optimally. Providing lactation management education to pregnant and post partum women is carried out with the aim of increasing knowledge and skills of correct breastfeeding, and overcoming problems in breastfeeding, as well as the importance of breastfeeding to reduce stunting rates. Lactation management education is part of Community Service activities with the target group namely pregnant women and post partum mothers in Sri Meranti Village, Rumbai District, Pekanbaru City. Educational activities are carried out using the interactive lecture method, with educational material related to lactation management, correct breastfeeding positions, how to express breast milk, express breast milk, problems that arise during breastfeeding, breast massage, the benefits of breast milk in preventing stunting. The media used is a leaflet given to the target group. The result of this educational activity is that there is an increase in the knowledge and skills of pregnant women and postpartum women by 23%. The increase in the knowledge and skills of the target group shows the importance of conducting regular educational activities for pregnant women and post partum mothers so that they not only increase the coverage of exclusive breastfeeding, but also improve the quality of breastfeeding while preventing and reducing the incidence of stunting